Answer:
no solution
Step-by-step explanation:
5x - 8(x + 5) = 6 - 3x
Remember to follow PEMDAS. Note the equal sign, what you do to one side, you do to the other.
First, distribute -8 to all terms within the parenthesis
-8(x + 5) = (-8)(x) + (-8)(5) = -8x - 40
5x - 8x - 40 = 6 - 3x
Isolate the variable (x). Add 3x & 40 to both sides
5x - 8x (+3x) - 40 (+40) = 6 (+40) - 3x (+3x)
5x - 8x + 3x = 6 + 40
Simplify. Combine like terms
(5x - 8x + 3x) = (6 + 40)
0 = 46 ; False 0 ≠ 46 ∴ no solution is your answer
~
Answer:
Quadratic polynomial is x^2 - x - 20
Answer:
Step-by-step explanation:
A scalar is a constant value that is multiplied throughout a matrix.
e.g.
In number 1 the set up would look like this
3 * ![\left[\begin{array}{ccc}3&-1&5\\2&1&-4\\-6&3&2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%26-1%265%5C%5C2%261%26-4%5C%5C-6%263%262%5Cend%7Barray%7D%5Cright%5D)
To solve this, you must distribute the 3 to each value within the matrix
The solution to #1 would be
M = ![\left[\begin{array}{ccc}9&-3&15\\6&3&-12\\-18&9&6\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D9%26-3%2615%5C%5C6%263%26-12%5C%5C-18%269%266%5Cend%7Barray%7D%5Cright%5D)
The line plot shows it increases
Answer:
It would be B & E
Step-by-step explanation: